1998
DOI: 10.1002/jlb.63.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Activated T lymphocytes induce degranulation and cytokine production by human mast cells following cell-to-cell contact

Abstract: Activated mast cells reside in close apposition to T cells in some inflammatory processes. In this study, we analyzed whether this close physical proximity affects human mast cell degranulation and cytokine release. Thus HMC-1 human mast cells or primary bone marrow-derived human mast cells were cocultured with activated and with resting T cells. Mast cells cocultured with activated T cells released histamine and ␤-hexosaminidase and produced tumor necrosis factor ␣ (TNF-␣), an effect that peaked at 20 h. Kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 25 publications
(19 reference statements)
3
73
1
Order By: Relevance
“…Previous studies have also shown that MC maturation and activation is regulated by various products (interleukin-3 and 4) of T-lymphocytes (26), whereas MC derivatives such as histamine, tryptase, chymase, TNF-␣, and interleukins enhance inflammatory cell transmigration, maturation, and cytokine-release (2,27). Previous reports suggested the involvement of apoptosis of either renal host cells (28) or T-cells (29) in the pathogenesis of both human and experimental renal amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that MC maturation and activation is regulated by various products (interleukin-3 and 4) of T-lymphocytes (26), whereas MC derivatives such as histamine, tryptase, chymase, TNF-␣, and interleukins enhance inflammatory cell transmigration, maturation, and cytokine-release (2,27). Previous reports suggested the involvement of apoptosis of either renal host cells (28) or T-cells (29) in the pathogenesis of both human and experimental renal amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, purified populations of mast cells can present Ags to T cells by either MHC class I-or class II-restricted mechanisms in vitro (8 -11), and contact with activated T cells in vitro can induce some mast cell populations to secrete histamine, TNF, and metalloproteinase 9 and to exhibit enhanced levels of IL-4 mRNA (12)(13)(14)(15). Besides representing a major potential source of TNF (16,17), which can have several effects that influence T cell recruitment, activation, and function (18 -21), at least some mast cells can produce many other factors, including CCL2, CCL3, CCL4, CCL5, XCL1, IL-16, and leukotriene B 4 , which also have the potential to enhance T cell recruitment to local inflammatory sites (5,(22)(23)(24)(25).…”
Section: Ast Cells Represent Important Effector Cells In Th2-andmentioning
confidence: 99%
“…Such conditions can be induced by exposing mast cells to activated T cells. Specifically, we have previously demonstrated that direct and prolonged contact between HMCs and PMA-activated T cells induces mast cell activation, resulting in degranulation and release of cytokines (17), metalloproteinases (9), and fibrotic factors such oncostatin-M (18). We further showed that contact with membranes derived from activated T cells suffices to achieve maximal activation (9).…”
Section: All1 Inhibits T Cell Membrane-induced Activation Of Mast Cellsmentioning
confidence: 99%